Iqbal On Inner Religious Experience (Revisited) - Dr. Qazi, M. H; Dr.M.H. Qazi (Lahore Iqbal Academy Pakistan, 2008)
This book is essentially an investigation into the single theme of inner religious experience set of forth by Iqbal in his book The Reconstruction of Religious thoughts in Islam. In sympathy with this them, the book focuses on such related issues as (a) the nature of soul, (b) the mind body dualism, (c) the survival of soul after death, (d) the freedom of ego, (g) the nature of thought and being, (f) the relation of higher consciousness and ego and (g) the existence of of serial juxtaposition of divine time and divine and space.
Include References.
Keywords: Iqbal, Muhammad, Sir, 1877-1938 Criticism and interpretation